2016
DOI: 10.1007/978-3-319-46230-1_6
|View full text |Cite
|
Sign up to set email alerts
|

(Re)-Learning the City for Intergenerational Exchange

Abstract: Two major international agendas are currently working to realign social, material and representational elements of the city in ways that are helpful for both children and older adults. The Age Friendly City movement (AFC) (led by the World Health Organisation) and the Child Friendly Cities (CFC) movement (led by UNICEF) aim to ensure that planners, policy makers and developers design cities that take account of the interests of age groups who are too often marginalised in current policy and design processes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…This has, in turn, led to reductions in social capital which, they reported, can be disproportionately felt by older adults and young children, especially within age-segregated neighbourhoods. Manchester and Facer [126] identified that over the last two decades, interaction between generations in public spaces has diminished: positive contact have reduced as children and older adults alike are encouraged to live and spend time in age-segregated spaces where physical barriers such as gates and high walls predominate. They reported that fear and competition over resources and policies have also contributed to our cities becoming increasingly segregated on generational lines (p. 5).…”
Section: Poor Mental Healthmentioning
confidence: 99%
“…This has, in turn, led to reductions in social capital which, they reported, can be disproportionately felt by older adults and young children, especially within age-segregated neighbourhoods. Manchester and Facer [126] identified that over the last two decades, interaction between generations in public spaces has diminished: positive contact have reduced as children and older adults alike are encouraged to live and spend time in age-segregated spaces where physical barriers such as gates and high walls predominate. They reported that fear and competition over resources and policies have also contributed to our cities becoming increasingly segregated on generational lines (p. 5).…”
Section: Poor Mental Healthmentioning
confidence: 99%
“…Walking and mobility within the immediate environment are particularly relevant when engaging older adults. In the context of co-creation with older adults, it relates to the importance of ageing in place and neighbourhood (Wiles et al , 2012; Manchester and Facer, 2016). A study conducted by Wiles et al (2012) characterises “ageing in place” by the positive perceptions of older adults as a sense of attachment and social connection, a sense of security and familiarity and a sense of identity, linked to independence and autonomy.…”
Section: Related Work: Co-creating Digital Public Servicesmentioning
confidence: 99%
“…Motivated by these findings, researchers have increasingly recognized the need to support the health, safety, and wellbeing of city dwellers across the age spectrum, including children and older adults (Thang and Kaplan, 2012;Cushing and van Vliet, 2016). Age-friendly and child-friendly cities approaches emphasize the role of the built environment in addressing the vulnerability of urban youth and older adults and have been endorsed by the WHO and the United Nations Children's Fund (Manchester and Facer, 2017). Some scholars argue, however, that these two approaches have not converged in practice, often prioritizing the needs of a single age-group rather than embracing shared interests across the age spectrum (Biggs and Carr, 2015;Manchester and Facer, 2017).…”
Section: Intergenerational Public Space and Universal Designmentioning
confidence: 99%
“…Age-friendly and child-friendly cities approaches emphasize the role of the built environment in addressing the vulnerability of urban youth and older adults and have been endorsed by the WHO and the United Nations Children's Fund (Manchester and Facer, 2017). Some scholars argue, however, that these two approaches have not converged in practice, often prioritizing the needs of a single age-group rather than embracing shared interests across the age spectrum (Biggs and Carr, 2015;Manchester and Facer, 2017).…”
Section: Intergenerational Public Space and Universal Designmentioning
confidence: 99%